If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 100 = -5x + 900 Reorder the terms: 100 + 3x = -5x + 900 Reorder the terms: 100 + 3x = 900 + -5x Solving 100 + 3x = 900 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 100 + 3x + 5x = 900 + -5x + 5x Combine like terms: 3x + 5x = 8x 100 + 8x = 900 + -5x + 5x Combine like terms: -5x + 5x = 0 100 + 8x = 900 + 0 100 + 8x = 900 Add '-100' to each side of the equation. 100 + -100 + 8x = 900 + -100 Combine like terms: 100 + -100 = 0 0 + 8x = 900 + -100 8x = 900 + -100 Combine like terms: 900 + -100 = 800 8x = 800 Divide each side by '8'. x = 100 Simplifying x = 100
| 7x+28=70 | | 7x+14=2x+18 | | 14-18=40 | | 54+18x= | | 5.6+2.5=.9r | | 4+10=72 | | 16=-16t^2+16t+32 | | -15n+17=-14n-2 | | 7.8=23.4 | | 5(9.5-8h)=-20.5 | | 18-22=120 | | 4-11=120 | | 20a^2-15a= | | 3k+4+6k=-8+8k | | 3-8=35 | | m-4=22 | | 5+5+5=3x | | 17x-7+20x+15x+12x-17=360 | | 4ax-3b=b+20 | | -8d=80 | | 2-u=78 | | 7-9[7-(7y-4)]=0 | | x^4-2x^3+6x^2+8x-27=0 | | 11-18=63 | | -59+-2x=21-7x | | 4+3n=61 | | -[7z-(12z+4)]=4+(4z+1) | | (7p+2)3+8p= | | 8p^2+37p-15=0 | | 6+2=72 | | -10+5(c-3)=20 | | 2-(4x-7)=9-4x |